Nurses' perceptions of workplace culture in primary health care in Finland. (26th July 2015) - Hahtela, N.; Paavilainen, E.; McCormack, B.; Helminen, M.; Slater, P.; Suominen, T.
Abstract : Aim: This study aimed to describe nurses' perceptions of workplace culture, especially in regard to stress levels, job satisfaction and the practice environment in primary health care. Background: Health care is facing many challenges related to its attractiveness as a place of employment and the maintenance of a sufficient workforce supply. Previous studies report increasing rates of nurse job dissatisfaction and intentions to leave their current positions both in Finland and also globally. Improving workplace culture is thus vital in meeting the challenges related to recruitment and retention. Methods: A cross‐sectional descriptive design was used to describe nurses' perceptions of workplace culture. Data were collected by questionnaire from 22 units in nine primary healthcare organizations in Finland, and analysed using descriptive and inferential statistics. Results: Most of the respondents indicated that they were not certain whether their workplace culture was either positive or negative. Profession, age and work shift characteristics had an effect on the respondents' perceptions of workplace culture. Younger licensed practical and registered nurses assessed their workplace culture more positively, whereas older registered nurses and those working rotating rosters viewed workplace culture more negatively. Conclusions: The findings suggest that both unit and demographic characteristics affect workplace culture. This survey highlights that a positive workplace culture is one of the key factors in retaining and recruiting nurses, and provides an essential evidence that may be considered by other healthcare organizations. Implications for nursing and health policy: Nurse managers and healthcare leaders need to address workload management and take into account the related variables that affect a unit's workplace culture.